Lemmus schisticolor - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Lemmus schisticolor (Lilljeborg, 1844). Ofv. Kongl. Svenska Vet.-Akad. ForhandL Stockholm, 1:33. REVIEWED BY: M. Andera (MA). TYPE LOCALITY: Norway, Gulbrandsdal, Mjosen, near Lillehammer. DISTRIBUTION: Coniferous forest from Norway and Sweden through Siberia to Kolyma River and Kamchatka (U.S. S. R.), south to the Altai, N. Mongolia, Heilungkiang (China), and the Sikhote Alin Range; perhaps Sakhalin Isl. (U.S. S.R.). COMMENT: Transferred to Lemmus from Myopus by Chaline and Mein, 1979. Koenigswald and Martin, in press, Bull. Carnegie Mus. Nat. Hist., also place this species in Lemmus on the basis of the pattern of molar enamel. ISIS NUMBER: 5301410008081001001 as Myopus schisticolor. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on pages 488-489, DOI: 10.5281/zenodo.7353034